Development of Vibration Energy Harvesting for Drone Application - Ab Ghafar, Muhamad Badrul Amin (Universiti Teknologi PETRONAS, 2020)
This report explains on how to utilize wasted energy which is vibration energy that produced by a drone during flight for powering the low voltage device which is the LED to represent a drone application. Piezoelectric transducer will be used as the mechanism to do the conversion from vibration energy to electrical energy. Mathematical modelling utilizing the piezoelectric transducer to do the conversion will be carried out in MATLAB. Result of simulation is important to focus on our selection of drone before running the experiment. On the other hands, Energy harvester (EH300A) will be the Power Management Unit (PMU) to regulate or control the output voltage from piezoelectric to the application used in this project. There are numbers of experiment will be performed to develop and optimize the harvesting of energy from the drone which is testing the ability of piezoelectric transducer, weightlifting experiment of the drone, one-way air flow reacts on the piezoelectric transducer consistently by using mini portable fan, experiment using Drone propeller with Arduino by varying the speed and performed actual test on the drone.